Histoires d'Ailleurs : artistes et penseurs de l'itinérance. - Baqué, Dominique (Paris : Editions du Regard Paris, 2006)
Long, Richard ; Fulton, Hamish ; Kanayama, Akira ; Lane, Abigail ; Orozco, Gabriel ; Adams, Dennis ; Malone, Laurent ; Brouwn, Stanley ; Beuys, Joseph ; Cadere, Andre ; Guilleminot, Marie-Ange ; Alys, Francis ; Stalker
boek